Pengaruh Promosi Dan Brand Image Terhadap Keputusan Pembelian Handphone Iphone Pada Mahasiswa Program Studi Administrasi Bisnis Institut Stiami - Holifah; Irfan Setiawan (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The use of iPhones among university students remains high despite the availability of many other smartphones offering similar features. This phenomenon suggests that promotion and brand image play a role in influencing purchasing decisions. Based on this, the research formulates three main research questions: (1) To what extent does promotion influence the decision to purchase an iPhone among students of the Business Administration Study Program at Institut STIAMI? (2) To what extent does brand image influence the decision to purchase an iPhone among these students? (3) To what extent do promotion and brand image jointly influence the decision to purchase an iPhone among these students? This research uses a quantitative method with a descriptive approach. The sample consists of 120 student respondents who either currently use or are interested in purchasing an iPhone. Data were collected through questionnaires and analyzed using multiple linear regression and SPSS software. The results indicate that both promotion and brand image have a positive and significant effect on iPhone purchase decisions. These findings highlight the importance of effective marketing strategies and a strong brand image in shaping consumer purchasing decisions, particularly among students. Keywords: Promotion, Brand Image, Purchase Decision.